False-Positive Head-Impulse Test in Cerebellar Ataxia - Kremmyda, Olympia; Kirchner, Hanni; Glasauer, Stefan; Brandt, Thomas; Jahn, Klaus; Strupp, Michael (Frontiers in Neurology, 2012)
Abstract: The objective of this study was to compare the findings of the bedside head impulse test (HIT), passive head rotation gain, and caloric irrigation in patients with cerebellar ataxia (CA). In 16 patients with CA and bilaterally pathological bedside HIT, VOR gains were measured during HIT and passive head rotation by scleral search coil technique. Eight of the patients had pathologically reduced caloric responsiveness, while the other eight had normal caloric responses. Those with normal calorics showed a slightly reduced HIT gain (mean±SD: 0.73±0.15). In those with pathological calorics, gains 80ms and 100 ms after the HIT as well as the passive rotation VOR gains were significantly lower. The corrective saccade after head turn occurred earlier in patients with pathological calorics (111±62 ms after onset of the HIT) than in those with normal calorics. (191±17 ms, p=0.0064) We indentified two groups of patients with CA: those with an isolated moderate HIT deficit only, probably due to floccular dysfunction, and those with combined HIT, passive rotation and caloric deficit, probably due to a peripheral vestibular deficit. From a clinical point of view, these results show that the bedside HIT alone can be false positive for establishing a diagnosis of a bilateral peripheral vestibular deficit in patients with CA.